SHALAT BERJAMAAH SEBAGAI UPAYA RESILIENSI SISWA MI NURUL ATHHAR BANYUWANGI - Nur Faiz Habibah; Erlin Indaya Ningsih; Naim Hikmatut Thoyibah (SIRAJUDDIN : Jurnal Penelitian dan Kajian Pendidikan Islam, 2023)
Student resilience is crucial to be taught from an early age, as the challenges in studentlearning continue to increase. Resilience is not only achievable during the teenage years;even children can develop resilience if the educational environment provides early learningexperiences. This research adopts a qualitative descriptive approach, specifically employinga case study research design. Both primary and secondary data sources are utilized. Datacollection methods include interviews, observations, documentation, and data analysistechniques employ the Mills and Huberman analysis model.The findings of this study reveal that students at MI Nurul Athhar exhibit resilience at theirage, particularly through group prayers, which offer benefits ranging from the sources of "Ihave, I am, and I can." These benefits can be applied by students, as congregational prayersprovide various resources, encouraging them to be independent, responsible, and managetheir emotions.